Postmigrational Evolution of Polymicrogyria - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
A first in vivo MRI documentation of the postmigrational postnatal evolution of a case of polymicrogyria is reported from the Children's Hospital, Boston, MA.